La prioridad de la inversión de los recursos generados por la minería en beneficio del Estado en la atención de las necesidades de la población asentada en los territorios de exploración y explotación. Propuesta de Reforma a los arts. 22 y 23 de Ley de Minería - Aguinsaca Enríquez, Fredy Vicente (2016)
This paper legal research prior to obtaining a law degree and Bachelor of jurisprudence, analyzes the following problem: "The Ecuadorian State guarantees the rights of people in many ways to that prevailing provided in our Constitution of the Republic which provides protects and guarantees primarily the right to good living and a healthy environment, ensuring the resources of the same grant the people the basic and necessary means for their development, starting from this point Article 408 of the Constitution states that natural resources are inalienable, and indefeasible State nonrenewable natural resources and property, in general, mineral products, minerals and hydrocarbons, substances whose nature is different from the soil, even those who are in the areas covered by the waters of the territorial sea and maritime zones; as well as biodiversity and genetic heritage and the radio spectrum. These assets may be exploited only in strict compliance with environmental principles established in the Constitution. The State will participate in the benefits of the use of these resources, in an amount not less than the company that exploits. The State shall ensure that the mechanisms of production, consumption and use of natural resources and energy preserve and recover natural cycles and allow living with dignity; however, it can be seen that at present the resources generated by mining are used in large scale for the benefit of the same company that operates or explore certain territories leaving the place where these farms is done in complete neglect and helplessness at not completely fulfilled the established and guaranteed by our law "; which is part of the problematic field of Legal Sciences, so the importance of this research lies in the reality that is 5 observed today in relation to the need to implement a percentage of payment by private concessionaires will be used for investment of mineral resources obtained from mining in the development of social activities for the benefit and care needs of the population living in the territories of exploitation. My research work is structured as follows: the first frame is called "conceptual framework" in which issues of vital importance as fundamental concepts such as the right Miner, Mine, deposits and mineral resources are developed and also what is the mining property and consisting exploration and exploitation culminating this framework with the Mining Cadastre and Public Utility. The second part is called "Doctrinal Framework" which includes important topics such as the history of the Mining Law, the General Law on Mining Organization, likewise the legal classification of wealth Mining, Characteristics of concessions for mining and underground storage acceptances and origin, the mere act of granting the right to explore or mine, also discussed what accessories are the property of mining concessions, the shape and orientation of the concessions, the material object of mining concessions One of the important topics of this thesis as are the impacts of the mining industry, mining Agency for Regulation and Control, Extinction of the Mining Rights Forfeiture of the Concession and the permissions and finally Royalty payments . The third part is called "Legal Framework" in which consist vital issues related to the research topic as domestic legislation governing the mining right as the Constitution of the Republic and the Mining Act and the 6 Environmental Management Act. Similarly the corresponding analysis of Comparative Law as it relates to the topic being specifically developed in Legislation Costa Rica, Colombia and Paraguay is performed. Field research which includes important topics such as analysis of survey results and analysis of results of interviews, verification of objectives, hypothesis testing, doctrinal and legal support is also performed. And finally the last chapter in which the Conclusions and Recommendations and Proposed Reform which is aimed at reforming the Mining Law is ststated